2021
DOI: 10.1121/10.0005045
|View full text |Cite
|
Sign up to set email alerts
|

Localization of tones in a room by moving listeners

Abstract: It is difficult to localize the source of a tone in a room because standing waves lead to complicated interaural differences that become uninterpretable localization cues. This paper tests the conjecture that localization improves if the listener can move to explore the complicated sound field over space and time. Listener head and torso movements were free and uninstructed. Experiments at low and high frequencies with eight human listeners in a relatively dry room indicated some modest improvement when listen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Such scanning is evident in A-only for the frontal target ( Figure 3 ) in which trajectories are more complex than trajectories in the AV condition and self-rotations at the end of the target sentence show higher normalized variance in A-only than AV, possibly because the target was more difficult to localize. Macaulay and Hartmann (2021) analyzed sound localization strategies of sitting people in a task with unrestricted head movements and showed that people integrate and weight localization cues to guide their behavior. In the present study, the task was to understand speech from various target locations and respond with self-rotation as if somebody was talking to the participant, which inherently includes both sound localization and speech perception.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such scanning is evident in A-only for the frontal target ( Figure 3 ) in which trajectories are more complex than trajectories in the AV condition and self-rotations at the end of the target sentence show higher normalized variance in A-only than AV, possibly because the target was more difficult to localize. Macaulay and Hartmann (2021) analyzed sound localization strategies of sitting people in a task with unrestricted head movements and showed that people integrate and weight localization cues to guide their behavior. In the present study, the task was to understand speech from various target locations and respond with self-rotation as if somebody was talking to the participant, which inherently includes both sound localization and speech perception.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the task was to understand speech from various target locations and respond with self-rotation as if somebody was talking to the participant, which inherently includes both sound localization and speech perception. It is possible that people used a similar strategy for guiding behavior in the current experiment as in the experiments by Macaulay and Hartmann (2021) . However, this search and localize behavior is likely to be dominant in the A-only condition, while the appearance of the visual cue might have triggered another strategy.…”
Section: Discussionmentioning
confidence: 99%